PELAKSANAAN FUNGSI DINAS TENAGA KERJA DALAM PENYALURAN TENAGA KERJA DI KOTA PEKANBARU - Paraswati, Indah; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Labor constraints can be identified are: 1) Many companies disseminate job informationand recruitment alone without cooperating with Dinsosnakertrans. 2) Many job seekers whochoose to work too selective in choosing only bona fide jobs and high-paying. 3) The growth ofthe labor force that is faster than the growth of employment opportunities available. 4) Lack ofcommunication between providers working with job seekers. The formulation of the mainproblem in this research are: 1) How the implementation of the Department of Labor function inthe distribution of labor in the city of Pekanbaru? 2) factors that support the Department of Laborin the distribution of labor in the city of Pekanbaru. 3) How can private companies in Pekanbaruhelp program the Department of Labor in the distribution of labor in the city of Pekanbaru?This study used qualitative research methods to understand the phenomenon or a socialphenomenon with more emphasis on the complete picture of the phenomenon under study thanmemperincinya become variables are interrelated. This research was conducted at the office ofthe Department of Labor Pekanbaru. The reason the researchers chose the Department of Laboroffice Pekanbaru. In this research is taken to be the informant is the researchers conductedinterviews with one person Head of the Department of Labor Pekanbaru, 1 secretary, they serveas key informants, plus 11 staff and 5 people. Types and Data Sources: Primary data is dataobtained directly from the respondents that the source was obtained directly from the results ofquestionnaires and interviews. Secondary data, ie data obtained through documents, monographs,data board, books and other research.Here the author provides conclusions of this research paper: 1) Implementation of theEmployment Policy in Pekanbaru one of which is owned by the Department of Labor Pekanbaru.Where as program managers who perform activities such as coaching, supervision, andplacement of the work units involved in the implementation of employment programs. 2)Supporting factors can help the course of any activity conducted labor market is the availabilityof funds, facilities and infrastructure are complete, and proficiency of its personnel or employeesof the Department of Labor Pekanbaru. 3) Cooperation between the private company with theDepartment of Labor Pekanbaru City in the distribution of labor, the labor market for online jobseekers provided by the private company through the Department of Labor Pekanbaru, theattachment of the job vacancy information canvassing work done Agency Labor Pekanbarubased on information submitted private companies, and most importantly, private companieshave consistently reported vacancies still existing or required the company to the Department ofLabor Pekanbaru city.Keywords: Function, Distribution